2007
DOI: 10.1038/sj.npp.1301321
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the cAMP/PKA/DARPP-32 Signaling Pathway is Required for Morphine Psychomotor Stimulation but not for Morphine Reward

Abstract: Activation of the cAMP/PKA pathway in the dopaminoceptive neurons of the striatum has been proposed to mediate the actions of various classes of drugs of abuse. Here, we show that, in the mouse nucleus accumbens and dorsal striatum, acute administration of morphine resulted in an increase in the state of phosphorylation of the dopamine-and cAMP-regulated phosphoprotein of 32 kDa (DARPP-32) at Thr34, without affecting phosphorylation at Thr75. The ability of morphine to stimulate Thr34 phosphorylation was preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 34 publications
4
32
0
Order By: Relevance
“…Locomotor sensitization was measured following a single injection of morphine (2.5 or 5 mg/kg) in wild type or knock-in DARPP-32 mutants (Figure 9). T34A mutant mice displayed a decreased locomotor response to the first injection of morphine (Figure 9A), as previously reported (Borgkvist et al , 2007). No sensitization was observed after the second injection of morphine at the two doses tested (Figure 9A).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Locomotor sensitization was measured following a single injection of morphine (2.5 or 5 mg/kg) in wild type or knock-in DARPP-32 mutants (Figure 9). T34A mutant mice displayed a decreased locomotor response to the first injection of morphine (Figure 9A), as previously reported (Borgkvist et al , 2007). No sensitization was observed after the second injection of morphine at the two doses tested (Figure 9A).…”
Section: Resultssupporting
confidence: 89%
“…Similarly, in knockin mutant mice in which Thr-34 was replaced by an alanine (T34A), a mutation, which prevents DARPP-32 from inhibiting protein phosphatase-1, sensitization to a single injection of cocaine was prevented (Valjent et al , 2005), whereas sensitization to repeated injections was increased (Zachariou et al , 2006). It has also been reported that sensitization to repeated injections of morphine was not significantly altered in null or T34A mutant mice (Borgkvist et al , 2007). Because of the apparent differences between sensitization to single and repeated injections in the DARPP-32 mutant mice, we tested TIPS for morphine in these mice.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…This response requires D1 receptors, the phosphoprotein DARPP32 (Becker et al, 2001;Borgkvist et al, 2007;Urs et al, 2011) and ERK (Borgkvist et al, 2008;Urs et al, 2011). We, and others, have shown that the locomotor effect of morphine is blunted in mice lacking b-arrestin 2 (Bohn et al, 2003;Urs et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are three main groups of GPCR subtypes: μ, δ and κ receptors. These have been shown to modulate several signalling pathways such as the cAMP pathway, Akt or MAPK-ERK pathways (Li and Chang, 1996;Borgkvist et al, 2007;Merighi et al, 2013). In the brain, both acute and chronic morphine results in either up-regulation or downregulation of ERK1/2 activity depending on the brain region, and induces c-fos and junB in striatum and nucleus accumbens (Liu et al, 1994;Ortiz et al, 1995;Berhow et al, 1996;Eitan et al, 2003).…”
Section: Tables Of Linksmentioning
confidence: 99%